The Role of Organizational Commitment in Mediating the Effect of Employee Agility and Organizational Support on Readiness for Change among Employees of BNN NTB Province - Jayadi, M. Ramdoni; Suryatni, Mukmin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the effect of employee agility and perceived organizational support on readiness for change, with organizational commitment as a mediating variable among employees of the National Narcotics Board (BNN) in West Nusa Tenggara Province. Using a quantitative, explanatory research design, data were collected through a census survey of 54 active employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results reveal that organizational commitment significantly influences readiness for change. While employee agility and organizational support do not directly affect readiness for change, both have significant indirect effects through organizational commitment. These findings highlight the critical role of psychological commitment in fostering change readiness. The study contributes to change management literature and offers practical implications for enhancing organizational transformation strategies in public institutions.